PROTOCOL: Exploring the effect of case management in homelessness per components: A systematic review of effectiveness and implementation, with meta‐analysis and thematic synthesis. Issue 1 (23rd February 2022) - Weightman, Alison L.; Kelson, Mark J.; Thomas, Ian; Mann, Mala K.; Searchfield, Lydia; Hannigan, Ben; Smith, Robin J.; Willis, Simone; Cordiner, Rhiannon
Abstract: This is the protocol for a Campbell review. The objectives are as follows: To carry out a mixed methods review to summarise current evidence relating to the components of case‐management interventions for people experiencing homelessness.